A metal dielectric enhanced reflection film with a wavelength of 3-5µm and a preparation method thereof

By preparing a 3-5 µm wavelength metal dielectric reinforced reflective film composed of Cr, Au, Y2O3, ZnSe and YF3 layers on an optical glass substrate, the problem of insufficient reflectivity in the prior art is solved. , achieving high reflectivity and high sensitivity gas detection effect.

CN119200061BActive Publication Date: 2025-02-18WUHAN GANWEI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411700967.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-18
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing mid-infrared band high-reflection lenses are difficult to compatible with multiple gas detection, and the gold-plated lenses lack reflectivity in ultra-low concentration gas detection, which cannot meet the needs of high sensitivity and multi-gas detection.

Method used

Using K9 or BK7 double-sided polished optical glass as the substrate, a metal dielectric reinforced reflective film with a wavelength of 3-5 µm is prepared by high-temperature and low-vacuum coating method. The film layer structure includes Cr, Au, Y2O3, ZnSe and YF3 and other layers. Set a coefficient (a-q) of the appropriate quarter reference wavelength optical thickness to control the optical thickness of the film layer to achieve high reflectivity and stability.

Benefits of technology

A high-reverse dielectric film with a reflectivity of ≥99.5% in the 3-5µm band is achieved, which improves the sensitivity of the gas detection system and is compatible with the detection of a variety of greenhouse gases. The film layer has excellent mechanical properties, chemical stability and durability. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119200061B_ABST
    Figure CN119200061B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of optical films, and specifically discloses a metal dielectric enhanced reflective film with a wavelength of 3‑5µm and a preparation method thereof. The metal dielectric enhanced reflective film with a wavelength of 3‑5µm has a film layer structure of: Sub / aGbAcYdLeHfLgHhLiHjLkHlLmHnLoHpLqH / O, wherein Sub represents a BK7 or K9 substrate, O represents air, G represents a Cr layer, A represents an Au layer, Y represents a Y2O3 layer, H represents a ZnSe layer, and L represents a YF3 layer; a‑q represents the coefficient of the optical thickness of one quarter of the reference wavelength of each layer. The metal dielectric enhanced reflective film with a wavelength of 3‑5µm prepared in the present application uses K9 / BK7 double-sided polished optical glass as a substrate, and a metal dielectric film is plated on the surface of the substrate to obtain a metal dielectric enhanced reflective film with excellent mechanical and optical properties, which is suitable for infrared medium-wave prism optical imaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of optical films, and more specifically, to a metal medium enhanced reflective film with a wavelength of 3-5µm and a preparation method thereof. Background Art

[0002] In optical systems, metal-dielectric reflective film is a composite optical film that combines metal and dielectric materials. It is used to improve the reflectivity of light and control the path of light. This film is usually composed of one or more layers of high-reflectivity metals (such as silver, aluminum, gold, etc.) and dielectric materials (such as silicon dioxide, titanium oxide, etc.) stacked alternately. The metal layer provides basic high reflectivity, while the dielectric enhancement layer is used to provide higher reflectivity and protect the metal film layer from oxidation.

[0003] Metal dielectric enhanced reflective films with a wavelength of 3-5µm are usually used in the mid-infrared spectral region. This band has important applications in infrared imaging, gas detection, thermal imaging and remote sensing. At present, a wide-band high-reflective dielectric film is needed in the field of gas analysis, especially in the field of greenhouse gas detection (detection of CO / CO 2 / CH 4 Concentration), usually use mid-infrared band high-reflection lenses or gold-plated lenses for detection. Currently, most of the mid-infrared band high-reflection lenses on the market are for single gas detection and are not compatible with multiple gas detection. Or the gold-plated lenses (reflectivity of about 98%) cannot meet the requirements for ultra-low concentration gas detection.

[0004] In order to improve the sensitivity of the gas detection system and realize the detection of multiple greenhouse gases in the same system, it is urgently necessary to provide a high-reflective dielectric film with a reflectivity of ≥99.5% in the 3-5µm band. Summary of the invention

[0005] In order to improve the sensitivity of the gas detection system and realize the detection of multiple greenhouse gases by the same system, the present application provides a metal dielectric enhanced reflection film with a wavelength of 3-5µm and a preparation method thereof.

[0006] In the first aspect, the present application provides a metal dielectric enhanced reflective film with a wavelength of 3-5 μm, which adopts the following technical solution:

[0007] A metal dielectric enhanced reflection film with a wavelength of 3-5µm, the film layer structure is: Sub / aGbAcYdLeHfLgHhLiHjLkHlLmHnLoHpLqH / O, where Sub represents BK7 or K9 substrate, O represents air, G represents Cr layer, A represents Au layer, and Y represents Y 2 O 3 layer, H represents ZnSe layer, L represents YF 3 layer; aq represents the coefficient of the optical thickness of each layer at one quarter of the reference wavelength.

[0008] By adopting the above technical scheme, K9 or BK7 double-sided polished optical glass is used as a substrate, which has good optical transparency, high mechanical strength, thermal stability and chemical stability. A metal dielectric film is plated on the surface of the substrate to obtain a metal dielectric enhanced reflective film with excellent mechanical and optical properties, which is suitable for infrared medium-wave prism optical imaging.

[0009] Since the required reflection band is the mid-wave infrared band and the reflectivity requirement is high, Au mid-wave infrared band has good stability, high reflectivity and conductivity. Au is used as the main reflection coating material. In order to better ensure the density of the film layer, a Cr layer is added between the substrate and the Au layer. The Cr layer is used as an adhesion layer to enhance the adhesion between the substrate and the Au layer, which helps prevent the reflective film from stratifying or falling off during use, and ensures the stability and durability of the reflective film.

[0010] The dielectric enhancement layer uses ZnSe layer, YF 3 Multilayer film, improve the reflectivity, chemical stability, thermal stability and transparency of the reflective film, Y 2 O 3 The light transmittance range of the material is 0.25-8μm. As a transition layer between the reinforcing layer and the reflective layer film material, it can significantly enhance the adhesion of the film layer.

[0011] Optionally, the reference wavelength λ is 850 nm, the value range of a is 1.0-1.8, the value range of b is 0.13-0.16, the value range of c is 0.3-0.5, the value range of d is 3.7-3.9, the value range of e is 4.5-4.7, the value range of f is 4.4-4.6, the value range of g is 4.6-4.8, and the value range of h is 4.65-4. 85, the value range of i is 2.7-2.9, the value range of j is 1.4-1.6, the value range of k is 4.0-4.2, the value range of l is 4.5-4.7, the value range of m is 3.4-3.6, the value range of n is 1.1-1.3, the value range of o is 3.2-3.4, the value range of p is 0.4-0.6, and the value range of q is 0.2-0.4.

[0012] By adopting the above technical solution and setting the aq coefficient, the optical thickness of the thin film layer can be controlled so that the incident light produces an interference effect between the thin film layers, thereby achieving control over the reflected and transmitted light, ensuring that the entire thin film system has optimal performance within a specific wavelength range, and reducing the dispersion effect of the film at different wavelengths, ensuring that the film has stable optical properties within a wide band, and ensuring the performance stability, mechanical properties and durability of the film under long-term use or harsh environmental conditions.

[0013] Optionally, the physical thicknesses of each layer corresponding to aq are 48-52nm, 197-203nm, 47-49nm, 543-547nm, 383-387nm, 638-642nm, 390-392nm, 676-680nm, 230-234nm, 208-212nm, 343-347nm, 653-657nm, 291-295nm, 172-176nm, 272-276nm, 67-71nm, and 20-24nm respectively.

[0014] By adopting the above technical solution, the appropriate physical thickness is limited, corresponding to the aq coefficient, the control of reflected and transmitted light is achieved, the reflectivity of the reflective film is improved, and the optical properties, mechanical and chemical stability and durability of the film are ensured.

[0015] In a second aspect, the present application also provides a method for preparing a metal dielectric enhanced reflective film with a wavelength of 3-5µm, using a high-temperature low-vacuum coating method to prepare each film layer by ion-assisted deposition.

[0016] By adopting the above technical solution and the high-temperature low-vacuum coating method, the stress problem between film layers can be effectively solved, the density of the film layer can be improved, and the film layer can be made stronger and have a longer service life.

[0017] Ion-assisted deposition is used to prepare each film layer, which improves the density and uniformity of the film layer, reduces defects and pores in the film layer, increases the interaction between the film layer and the substrate, improves the adhesion of the film layer, and reduces the risk of film peeling during use; it also improves the film layer's resistance to chemical corrosion, extends the film layer's service life, and improves reflectivity, transmittance, conductivity, thermal stability, wear resistance and hardness.

[0018] Optionally, the substrate is cleaned before coating, using the following steps:

[0019] (1) Dispersing iron oxide powder in anhydrous ethanol and stirring evenly to obtain a polishing solution;

[0020] (2) Rolling up an absorbent cotton swab to obtain an absorbent cotton swab with a length of 4-5 cm, and polishing the substrate surface with the absorbent cotton swab dipped in polishing liquid for 2-3 minutes;

[0021] (3) Disperse ether in anhydrous ethanol and stir evenly to obtain a mixed solution. Use a cotton swab dipped in the mixed solution to wipe the substrate to remove residual dirt on the surface.

[0022] By adopting the above technical scheme, the polishing liquid composed of iron oxide powder and anhydrous ethanol is used for precision polishing of optical glass, semiconductor materials, metal surfaces, etc. The iron oxide powder, as a polishing agent, has good polishing effect and chemical stability, and can effectively remove dirt on the surface of the material; ethanol, as a solvent and lubricant, can help the iron oxide powder to be evenly dispersed, reduce friction during the polishing process, and at the same time take away the heat and debris generated during the polishing process, thereby maintaining the cleanliness of the polishing liquid and the polishing effect.

[0023] Polish the substrate surface with an absorbent cotton swab dipped in polishing liquid. The absorbent cotton swab has good liquid absorption and softness, can evenly carry the polishing liquid, and provide gentle mechanical friction during the polishing process to finely polish the surface, remove tiny scratches and roughness, and improve surface finish.

[0024] The mixed liquid obtained by dispersing ether in anhydrous ethanol has good solubility and volatility, and can effectively remove grease, dust, residues and microorganisms on the surface of the substrate. It can dry quickly after wiping to avoid leaving water stains or solvent residues. The surface activity of the cleaned substrate is improved, which is beneficial to subsequent processing processes such as bonding, coating, and welding.

[0025] Optionally, before evaporation, the Kaufman ion source cleans the substrate for 2-3 minutes, and the ion source parameters are set as follows: acceleration voltage 200V, plate voltage 400-600V, beam current 90-100mA.

[0026] By adopting the above technical solution, in order to better ensure the adhesion and further strengthen the adhesion between the substrate and the film layer, before evaporation, the Kaufman ion source cleans the substrate for 2-3 minutes, and the ion source parameters are set as: acceleration voltage 200V, screen voltage 400-600V, beam current 90-100mA. Remove stains on the substrate surface, increase the cohesion coefficient, and strengthen the adhesion of the film layer; during the deposition of the film layer, use the Kaufman ion source to assist deposition and increase the aggregation density.

[0027] Optional, initial vacuum degree is 8.0×10 -4 Pa, baking temperature is 150-190℃; ion source parameters are set as: acceleration voltage 200V, screen voltage 400-600V, beam current 80-150mA.

[0028] By adopting the above technical solution and setting various coating parameters within a certain range, the stress problem between film layers is effectively solved, the compactness of the film layer is improved, the film layer is more solid and has a longer life, the durability of the Au film to the environment is improved, and the surface finish of the substrate can be effectively maintained, and a metal dielectric reflective film with excellent optical properties, strong film adhesion and friction resistance is obtained. The reflective film reflects Ravg ≥ 99.5% in the infrared medium wave band (3-5µm).

[0029] Optional, Cr layer, Au layer, Y 2 O 3 Layer coating conditions: start coating at a constant temperature of 150-155℃ for 30-32min, without filling process gas to maintain vacuum greater than 5.0*10 -3 Pa.

[0030] By adopting the above technical solution, Cr layer, Au layer, Y 2 O 3 The coating conditions of the layer are as follows: the Cr layer is between the substrate and Au to increase the adhesion between the substrate and Au. Au (gold) is the reflective layer material with a reflectivity of ≥98%. The coating process is carried out at a constant temperature of 150-155°C. This temperature range helps to improve the uniformity and adhesion of the coating, while avoiding damage to the substrate material due to overheating; before starting the coating, the substrate needs to be preheated at the set temperature for 30-32 minutes. The purpose of preheating is to stabilize the substrate, reduce the temperature gradient, and improve the uniformity and quality of the coating.

[0031] Setting the substrate temperature can improve the crystallinity and density of the film layer, while not filling the process gas will improve the uniformity and adhesion of the film layer, and maintaining the vacuum degree greater than 5.0*10 -3 Pa helps to reduce the interference of gas molecules on the coating process, improve the purity and density of the coating, and also helps to improve the bonding strength between the coating and the substrate. The obtained film layer has good adhesion, corrosion resistance, conductivity and optical properties.

[0032] Optional, YF 3 The coating conditions of the ZnSe layer and the ZnSe layer are as follows: the coating is carried out at a constant temperature of 190-195°C for 30-33 minutes, using ion-assisted deposition and filling with argon (Ar).

[0033] By adopting the above technical solution, YF 3 The coating conditions of the ZnSe layer have a 3-5µm anti-reflection effect to improve the reflectivity of Au (gold); the coating process is carried out at a constant temperature of 190-195℃, which helps to improve the crystallization quality and adhesion of the coating, while ensuring the thermal stability of the substrate material; before starting the coating, the substrate needs to be preheated at the set temperature for 30-33 minutes. The purpose of preheating is to make the substrate reach a thermal equilibrium state, reduce the temperature gradient, and improve the uniformity and quality of the coating.

[0034] Ion-assisted deposition technology, by introducing high-energy ions to bombard the coating surface, can significantly improve the density and adhesion of the coating, while also improving the optical and mechanical properties of the coating; setting the substrate temperature can improve the crystallinity and density of the film layer.

[0035] Optionally, the evaporation rate of Cr is 0.3±0.1nm / s, the evaporation rate of Au is 0.5±0.05nm / s, and the evaporation rate of Y is 2 O 3 The evaporation rate of YF is 0.5±0.1nm / s. 3 The evaporation rate of is 1.2±0.05nm / s, and the evaporation rate of ZnSe is 1.2±0.05nm / s.

[0036] By adopting the above technical solution, the control of conditions during film preparation is very critical. The preparation conditions of each film layer not only affect the density and other properties of the single film layer, but also affect the bonding strength with the adjacent film layers and the optical properties of the overall film layer. Among them, the choice of evaporation rate is particularly important. The research and development process practice found that the evaporation rate of the five materials of the film system is the highest at the following evaporation rates, and the density of the film layer and the bonding strength of the adjacent film layers are the highest.

[0037] In summary, this application has the following beneficial effects:

[0038] 1. In this application, K9 or BK7 double-sided polished optical glass is used as the substrate, which has good optical transparency, high mechanical strength, thermal stability and chemical stability. A metal dielectric film is plated on the surface of the substrate to obtain a metal dielectric enhanced reflective film with excellent mechanical and optical properties, which is suitable for infrared medium-wave prism optical imaging.

[0039] 2. In this application, Au has good stability, high reflectivity and conductivity in the mid-wave infrared band. Au is used as the main reflective coating material. In order to better ensure the density of the film layer, a Cr layer is added between the substrate and the Au layer. The Cr layer is used as an adhesion layer to enhance the adhesion between the substrate and the Au layer, which helps prevent the reflective film from stratifying or falling off during use, thereby ensuring the stability and durability of the reflective film.

[0040] 3. The dielectric enhancement layer in this application uses ZnSe layer, YF 3 layer, improve the reflectivity, chemical stability, thermal stability and transparency of the reflective film, Y 2 O 3 The light transmittance range of the material is 0.25-8μm. As a transition layer between the reinforcing layer and the reflective layer film material, it can significantly enhance the adhesion of the film layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a design structure diagram of the 3-5µm metal dielectric enhanced reflective film layer in Example 1;

[0042] Figure 2 is a reflection curve diagram of the 3-5µm metal dielectric enhanced reflection film design in Example 1;

[0043] Figure 3 It is a partial enlarged view of the reflection curve of the 3-5µm metal dielectric enhanced reflection film design in Example 1;

[0044] Figure 4 It is a reflection curve diagram of the 3-5µm metal dielectric enhanced reflection film test in Example 1. DETAILED DESCRIPTION

[0045] Example 1

[0046] A metal dielectric enhanced reflection film with a wavelength of 3-5µm, the film layer structure is: Sub / aGbAcYdLeHfLgHhLiHjLkHlLmHnLoHpLqH / O, where Sub represents BK7, O represents air, G represents Cr layer, A represents Au layer, and Y represents Y 2 O 3 layer, H represents ZnSe layer, L represents YF 3 layer; aq represents the coefficient of the optical thickness of each layer at one quarter of the reference wavelength.

[0047] The reference wavelength λ is 850nm, the value range of a is 1.0, the value range of b is 0.13, the value range of c is 0.3, the value range of d is 3.7, the value range of e is 4.5, the value range of f is 4.4, the value range of g is 4.6, the value range of h is 4.65, the value range of i is 2.7, the value range of j is 1.4, the value range of k is 4.0, the value range of l is 4.5, the value range of m is 3.4, the value range of n is 1.1, the value range of o is 3.2, the value range of p is 0.4, and the value range of q is 0.2.

[0048] The physical thicknesses of the layers corresponding to aq are 48nm, 197nm, 47nm, 543nm, 383nm, 638nm, 390nm, 676nm, 230nm, 208nm, 343nm, 653nm, 291nm, 172nm, 272nm, 67nm, and 20nm. a corresponds to the aG layer, b corresponds to the bA layer, and so on.

[0049] The high-temperature low-vacuum coating method is adopted to prepare each film layer by ion-assisted deposition. The Tianyi Guotai TIV-850 coating machine is adopted, and the crystal control adopts the Molin MXC-3B controller. The thickness of the film mass is measured by the change of the quartz crystal oscillation frequency. The ion source adopts the Kaufman ion source to ionize the neutral atoms into ions. The ions are accelerated to obtain energy. By reasonably controlling the ion energy, the density of the deposited film can be improved, and the optical and mechanical properties can be improved. The vacuum chamber relies on the cooperation of the mechanical pump, Roots pump and molecular pump system to obtain the vacuum required by the experiment. The vacuum measurement system uses the low vacuum ZJ-52T resistance gauge and the high vacuum ZJ-27 ionization gauge to measure the vacuum degree. The correction mechanism in the vacuum chamber corrects the uniformity of the film layer to achieve the best effect.

[0050] Clean the substrate before coating using the following steps:

[0051] (1) Disperse 3 g of iron oxide powder in 250 mL of anhydrous ethanol and stir evenly to obtain a polishing solution;

[0052] (2) Rolling up an absorbent cotton swab to obtain an absorbent cotton swab with a diameter of 1 cm and a length of 4 cm, and polishing the substrate surface with the absorbent cotton swab dipped in polishing liquid for 3 min;

[0053] (3) Disperse 30 mL of ether in anhydrous ethanol and stir evenly to obtain a mixed solution. Use an absorbent cotton swab dipped in the mixed solution to wipe the substrate to remove residual dirt on the surface;

[0054] Among them, the mass ratio of ether to anhydrous ethanol is 3:1.

[0055] When cleaning, the initial vacuum degree is 8.0×10 -4 Pa, the baking temperature is 150℃; the ion source parameters are set as: acceleration voltage 200V, screen voltage 400V, beam current 80mA.

[0056] Before evaporation, the substrate was bombarded with ions for 2 minutes, and the substrate was bombarded with ions for 2 minutes to clean the stains on the substrate surface, improve the cohesion coefficient, and strengthen the adhesion of the film layer; the ion source parameters were set as: acceleration voltage 200V, screen voltage 400V, beam current 90mA. During the film deposition process, a Kaufman ion source was used to assist deposition to increase the aggregation density. During the film deposition process, Ar was filled when depositing the dL layer to the qH layer. Cr layer, Au layer, Y 2 O 3 Layer coating conditions: start coating after constant temperature at 150℃ for 30min, without filling process gas to maintain vacuum degree of 6.0*10 -3 Pa.

[0057] YF 3The coating conditions of the ZnSe layer are as follows: the coating is carried out at a constant temperature of 190°C for 30 minutes, ion-assisted deposition is adopted and argon (Ar) is filled in, and the beam current is 100 mA.

[0058] The evaporation rate of Cr is 0.2nm / s, the evaporation rate of Au is 0.45nm / s, and the evaporation rate of Y 2 O 3 The evaporation rate of YF is 0.6nm / s. 3 The evaporation rate of is 1.15nm / s, and the evaporation rate of ZnSe is 1.15nm / s.

[0059] Example 2

[0060] A metal dielectric enhanced reflection film with a wavelength of 3-5µm, the film layer structure is: Sub / aGbAcYdLeHfLgHhLiHjLkHlLmHnLoHpLqH / O, where Sub represents K9 substrate, O represents air, G represents Cr layer, A represents Au layer, and Y represents Y 2 O 3 layer, H represents ZnSe layer, L represents YF 3 layer; aq represents the coefficient of the optical thickness of each layer at one quarter of the reference wavelength.

[0061] The reference wavelength λ is 850nm, the value range of a is 1.8, the value range of b is 0.16, the value range of c is 0.5, the value range of d is 3.9, the value range of e is 4.7, the value range of f is 4.6, the value range of g is 4.8, the value range of h is 4.85, the value range of i is 2.9, the value range of j is 1.6, the value range of k is 4.2, the value range of l is 4.7, the value range of m is 3.6, the value range of n is 1.3, the value range of o is 3.4, the value range of p is 0.6, and the value range of q is 0.4.

[0062] The physical thicknesses of the layers corresponding to aq are 52nm, 203nm, 49nm, 547nm, 387nm, 642nm, 392nm, 680nm, 234nm, 212nm, 347nm, 657nm, 295nm, 176nm, 276nm, 71nm, and 24nm. a corresponds to the aG layer, b corresponds to the bA layer, and so on.

[0063] The high-temperature low-vacuum coating method is adopted to prepare each film layer by ion-assisted deposition. The Tianyi Guotai TIV-850 coating machine is adopted, and the crystal control adopts the Molin MXC-3B controller. The thickness of the film mass is measured by the change of the quartz crystal oscillation frequency. The ion source adopts the Kaufman ion source to ionize the neutral atoms into ions. The ions are accelerated to obtain energy. By reasonably controlling the ion energy, the density of the deposited film can be improved, and the optical and mechanical properties can be improved. The vacuum chamber relies on the cooperation of the mechanical pump, Roots pump and molecular pump system to obtain the vacuum required by the experiment. The vacuum measurement system uses the low vacuum ZJ-52T resistance gauge and the high vacuum ZJ-27 ionization gauge to measure the vacuum degree. The correction mechanism in the vacuum chamber corrects the uniformity of the film layer to achieve the best effect.

[0064] (1) Disperse 3 g of iron oxide powder in 250 mL of anhydrous ethanol and stir evenly to obtain a polishing solution;

[0065] (2) Rolling up an absorbent cotton swab to obtain an absorbent cotton swab with a diameter of 1 cm and a length of 5 cm, and polishing the substrate surface with the absorbent cotton swab dipped in polishing liquid for 3 min;

[0066] (3) Disperse 35 mL of ether in anhydrous ethanol and stir to obtain a mixed solution. Use an absorbent cotton swab dipped in the mixed solution to wipe the substrate to remove residual dirt on the surface;

[0067] Among them, the mass ratio of ether to anhydrous ethanol is 3:1.

[0068] When cleaning, the initial vacuum degree is 8.0×10 -4 Pa, the baking temperature is 190℃; the ion source parameters are set as: acceleration voltage 200V, screen voltage 600V, beam current 150mA.

[0069] Before evaporation, the substrate was bombarded with ions for 3 minutes, and the substrate was bombarded with ions for 3 minutes to clean the surface stains of the substrate, improve the cohesion coefficient, and strengthen the adhesion of the film layer; the ion source parameters were set as: acceleration voltage 200V, screen voltage 600V, beam current 100mA. During the film deposition process, a Kaufman ion source was used to assist deposition to increase the aggregation density. During the film deposition process, Ar was filled when depositing the dL layer to the qH layer. Cr layer, Au layer, Y 2 O 3 Layer coating conditions: start coating after constant temperature at 155℃ for 32min, without filling process gas to maintain vacuum degree of 6.0*10 -3 Pa.

[0070] YF 3 The coating conditions of the ZnSe layer and the ZnSe layer are as follows: the coating is carried out at a constant temperature of 195°C for 33 minutes, ion-assisted deposition is adopted and argon (Ar) is filled, and the beam current is 90 mA.

[0071] The evaporation rate of Cr is 0.4nm / s, the evaporation rate of Au is 0.55nm / s, and the evaporation rate of Y 2 O 3 The evaporation rate of YF is 0.4nm / s. 3 The evaporation rate of is 1.25nm / s, and the evaporation rate of ZnSe is 1.25nm / s.

[0072] Comparative Example 1

[0073] A metal dielectric enhanced reflective film with a wavelength of 3-5 μm, which is different from the embodiment 1 in that the Y 2 O 3 layer.

[0074] Comparative Example 2

[0075] A metal dielectric enhanced reflective film with a wavelength of 3-5 μm, which differs from embodiment 1 in that the Cr layer is omitted.

[0076] Performance Testing

[0077] The performance of the metal dielectric enhanced reflective films with a wavelength of 3-5 μm prepared in Example 1-2 and Comparative Example 1-2 was tested;

[0078] Figure 1 3-5 μm metal dielectric enhanced reflective film layer design structure diagram of Example 1, the film layer design structure is: Sub / aGbAcYdLeHfLgHhLiHjLkHlLmHnLoHpLqH / O, where Sub represents BK7, O represents air, G represents Cr layer, A represents Au layer, and Y represents Y 2 O 3 layer, H represents ZnSe layer, L represents YF 3 layer; aq represents the coefficient of the optical thickness of each layer at one quarter of the reference wavelength.

[0079] Optical performance test: The reflectivity of the film prepared in Example 1 was tested using an infrared spectrophotometer Spectrum100 (the test curve is shown in FIG. Figure 4 As shown in the figure), the obtained spectral curve meets the design requirements (the design curve is shown in Figure 2-3 As shown in the figure): The main reflective material of the reflective film is Au, and the dielectric enhancement layer is made of ZnSe and YF 3 For the two materials, the designed film system has a reflectivity of Ravg≥99.5% in the infrared band of 3-5μm, which is basically consistent with the design curve.

[0080] Film performance test: In order to ensure the reliability of optical components, according to the requirements of GJB2485-95 General Specification for Optical Films, the infrared internal reflection metal films of Examples 1-2 and Comparative Examples 1-2 were subjected to the following environmental tests in sequence:

[0081] (1) Surface finish inspection: During the inspection, a black screen was used as the background, and the light source was a 36V, 108W ordinary incandescent bulb. A 10× magnifying glass was used to observe under reflected light. The metal dielectric enhanced reflective films of Example 1-2 and Comparative Example 1-2 were tested and both met the 40 / 20 grade requirement.

[0082] (2) Abrasion resistance test: Wrap two layers of dry absorbent gauze around the rubber friction head, and rub the metal dielectric enhanced reflective film layers of Example 1-2 and Comparative Example 1-2 along the same trajectory under a pressure of 9.8 N for 500 reciprocating cycles. The film layers of Example 1-2 and Comparative Example 1 had no scratches or other damage, while the film layer of Comparative Example 2 fell off over a large area, indicating that the film layer prepared in Example 1-2 had excellent abrasion resistance.

[0083] (3) Immersion test: The film samples of Example 1-2 and Comparative Example 1-2 were completely immersed in deionized water. After one week, the film of Example 1-2 showed no abnormality, the film of Comparative Example 1 partially fell off, and the film of Comparative Example 2 fell off over a large area, indicating that the stress of the film of Comparative Example 1-2 was large, indicating that the film prepared in Example 1-2 had excellent water resistance.

[0084] (4) Salt spray test: 35°C ambient temperature, 5% NaCl concentration, continuous spraying for 12 h for two cycles, a total of 24 h, the film layers of Examples 1-2 and Comparative Example 1 showed no abnormalities, while the film layer of Comparative Example 2 fell off over a large area, indicating that the film layers prepared in Examples 1-2 have excellent salt spray resistance.

[0085] (5) High and low temperature test: -40℃ to +90℃ for ten cycles, each cycle for 30 min. The film layers of Examples 1-2 and Comparative Example 1 had normal firmness, while the film layer of Comparative Example 2 fell off over a large area, indicating that the film layers prepared in Examples 1-2 had excellent heat resistance.

[0086] (6) Adhesion test: A 3M tape with a width of 1 cm was used to adhere to the surface of the film layer of Examples 1-2 and Comparative Examples 1-4. After the tape was quickly pulled up from the edge of the part in the vertical direction of the surface, the layers of Examples 1-2 did not fall off or be damaged. The above process was repeated 50 times, and the film layer still did not fall off or be damaged, meeting the requirements of the infrared medium-wave lens 3.5-5um optical imaging system. The film layer of Comparative Example 1 fell off slightly from the edge, while the film layer of Comparative Example 2 fell off over a large area, indicating that the film layer prepared in Examples 1-2 has excellent adhesion.

[0087] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A metal dielectric enhanced reflective film with a wavelength of 3-5µm, characterized in that: Sub / aGbAcYdLeHfLgHhLiHjLkHlLmHnLoHpLqH / O; Where Sub represents BK7 or K9 substrate, O represents air, G represents Cr layer, A represents Au layer, Y represents Y2O3 layer, H represents ZnSe layer, and L represents YF3 layer; aq represents the coefficient of the quarter reference wavelength optical thickness of each layer; The reference wavelength λ is 850nm, the value range of a is 1.0-1.8, the value range of b is 0.13-0.16, the value range of c is 0.3-0.5, the value range of d is 3.7-3.9, the value range of e is 4.5-4.7, the value range of f is 4.4-4.6, the value range of g is 4.6-4.8, and the value range of h is 4.65-4.85 , the value range of i is 2.7-2.9, the value range of j is 1.4-1.6, the value range of k is 4.0-4.2, the value range of l is 4.5-4.7, the value range of m is 3.4-3.6, the value range of n is 1.1-1.3, the value range of o is 3.2-3.4, the value range of p is 0.4-0.6, and the value range of q is 0.2-0.

4.

2. The metal dielectric enhanced reflective film with a wavelength of 3-5 μm according to claim 1, characterized in that: The physical thicknesses of each layer corresponding to aq are 48-52nm, 197-203nm, 47-49nm, 543-547nm, 383-387nm, 638-642nm, 390-392nm, 676-680nm, 230-234nm, 208-212nm, 343-347nm, 653-657nm, 291-295nm, 172-176nm, 272-276nm, 67-71nm, and 20-24nm respectively.

3. A method for preparing a metallic dielectric enhanced reflective film with a wavelength of 3-5 μm according to any one of claims 1-2, characterized in that: The high-temperature low-vacuum coating method is adopted to prepare each film layer by ion-assisted deposition.

4. The preparation method according to claim 3, characterized in that: Clean the substrate before coating using the following steps: (1) Dispersing iron oxide powder in anhydrous ethanol and stirring evenly to obtain a polishing solution; (2) Rolling up an absorbent cotton swab to obtain an absorbent cotton swab with a length of 4-5 cm, and polishing the substrate surface with the absorbent cotton swab dipped in polishing liquid for 3-3.5 min; (3) Disperse ether in anhydrous ethanol and stir evenly to obtain a mixed solution. Use a cotton swab dipped in the mixed solution to wipe the substrate to remove residual dirt on the surface.

5. The preparation method according to claim 3, characterized in that: The initial vacuum degree is 8.0×10 -4 Pa, baking temperature is 150-190℃; ion source parameters are set as: acceleration voltage 200V, screen voltage 400-600V, beam current 80-150mA.

6. The preparation method according to claim 3, characterized in that: Before evaporation, the Kaufman ion source cleans the substrate for 2-3 minutes, and the ion source parameters are set as follows: acceleration voltage 200V, screen voltage 400-600V, beam current 90-100mA.

7. The preparation method according to claim 3, characterized in that: Plating conditions for Cr layer, Au layer and Y2O3 layer: start coating after constant temperature of 150-155℃ for 30-32min, do not fill process gas to maintain vacuum degree greater than 5.0*10 -3 Pa.

8. The preparation method according to claim 3, characterized in that: The coating conditions of the YF3 layer and the ZnSe layer are as follows: the coating is carried out at a constant temperature of 190-195°C for 30-33 minutes, using ion-assisted deposition and filling with argon gas.

9. The preparation method according to claim 3, characterized in that: The evaporation rate of Cr is 0.3±0.1nm / s, the evaporation rate of Au is 0.5±0.05nm / s, the evaporation rate of Y2O3 is 0.5±0.1nm / s, the evaporation rate of YF3 is 1.2±0.05nm / s, and the evaporation rate of ZnSe is 1.2±0.05nm / s.

Citation Information

Patent Citations

  • Infrared metal reflecting film with high adhesive force and manufacturing method thereof

    CN104090312A

  • Efficient gold reflective film suitable for 7.5-12-micrometer waveband and preparation method of efficient gold reflective film

    CN110850519A